Clinical Significance Of Serum HbeAg Among HbsAg Positive Patients - Islam, MDU; Ahmed, RU; Kabria, SG; Hossain, MT; Biswas, MK; Bhuiyan, MSR; Ahmed, NU; Haq, N (Faridpur Medical College Journal, 2011)
Hepatitis B Virus (HBV) infection is a menace worldwide as a major cause of morbidity & mortality through its consequences viz. acute hepatitis, chronic active, or persistent hepatitis, cirrhosis of liver and primary hepatocellular carcinoma. A total of 127 'HBsAg positive' patients were studied for 'HBeAg' by serum ELISA. Patient's aged between 11 to 60 years with a mean age 27.11. Out of 127 'HBsAg positive' cases 19 (14.96%) were 'HBeAg positive', of which maximum (21.43%) were among <20 years age group. Among 106 male patients 15 (14.155) & among 21 female patients 4 (19.055) were 'HBeAg positive'. Often the initiation of therapeutic approach remains a dilemma in absence of laboratory assessment of viraemic load or presence of HBV DNA through PCR or other DNA hybridization techniques. In such situations, alternatively, a significantly serum 'HBeAg' among 'HBsAg positive' patients may be taken as a surrogate marker for acute viral replication, and, thus apply justifying the initiation of antiviral chemotherapy without delay. DOI: 10.3329/fmcj.v5i2.6821 Faridpur Med. Coll. J. 2010;5(2):50-52